Risk factors for inadequate prenatal care use in the metropolitan area of Aracaju, Northeast Brazil - Ribeiro, Eleonora Ramos de Oliveira (2009)
Background: The aim of prenatal care is to promote good maternal and foetal health and to identify risk factors for adverse pregnancy outcomes in an attempt to promptly manage and solve them. Although high prenatal care attendance is reported in most areas in Brazil, perinatal and neonatal mortalities are disproportionally high, raising doubts about the quality and performance of the care provided. The objective of the present study was to evaluate the adequacy of prenatal care use and the risk factors involved in inadequate prenatal care utilization in the metropolitan area of Aracaju, Northeast Brazil. Methods: A survey was carried out with puerperal women who delivered singleton liveborns in all four maternity hospitals of Aracaju. A total of 4552 singleton liveborns were studied. The Adequacy of Prenatal Care Utilization Index, modified according to the guidelines of the Prenatal Care and Birth Humanization Programme, was applied. Socioeconomic, demographic, biological, life style and health service factors were evaluated by multiple logistic regression. Results: Prenatal care coverage in Aracaju was high (98.3%), with a mean number of 6.24 visits. Prenatal care was considered to be adequate or intensive in 66.1% of cases, while 33.9% were considered to have inadequate usage. Age < 18 to 34 years at delivery, low maternal schooling, low family income, two or more previous deliveries, maternal smoking during pregnancy, having no partner and prenatal care obtained outside Aracaju were associated with inadequate prenatal care use. In contrast, private service attendance protected from inadequate prenatal care use. Conclusion: Prenatal care coverage was high. However, a significant number of women still had inadequate prenatal care use. Socioeconomic inequalities, demographic factors and behavioural risk factors are still important factors associated with inadequate prenatal care use.